2008
DOI: 10.1007/s00239-008-9159-4
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Conservation and Context in TGFβ and Wnt Signaling Suggest New Targets and General Themes for Posttranslational Modification

Abstract: TGFb and Wnt pathways play important roles in the development of animals from sponges to humans. In both pathways posttranslational modification as a means of regulating their function, such as lysine modification by ubiquitination and sumoylation, has been observed. However, a gap exists between the immunological observation of posttranslational modification and the identification of the target lysine. To fill this gap, we conducted a phylogenetic analysis of lysine conservation and context in TGFb and Wnt pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Monoubiquitination of Smad4 occurs on Lys-507 in the MH2 domain and leads to improved transcriptional TGFb signaling [63], but also promotes export of Smad4 to the cytoplasm [67]. In addition to the so-called "universally conserved Smad lysine", which corresponds to Lys-507 in Smad4, Lys-519 is a unique lysine residue in Smad4 and is well-conserved across species as suggested by recent phylogenetic evidence [68]. Whether Lys-519 can also act as an acceptor site for monoubiquitination is currently unknown but remains possible as mutation of Lys-507 indicated the presence of a weak secondary mono-ubiquitination site in the Smad4 MH2 domain [63].…”
Section: Regulation Of Co-smad Stabilitymentioning
confidence: 98%
“…Monoubiquitination of Smad4 occurs on Lys-507 in the MH2 domain and leads to improved transcriptional TGFb signaling [63], but also promotes export of Smad4 to the cytoplasm [67]. In addition to the so-called "universally conserved Smad lysine", which corresponds to Lys-507 in Smad4, Lys-519 is a unique lysine residue in Smad4 and is well-conserved across species as suggested by recent phylogenetic evidence [68]. Whether Lys-519 can also act as an acceptor site for monoubiquitination is currently unknown but remains possible as mutation of Lys-507 indicated the presence of a weak secondary mono-ubiquitination site in the Smad4 MH2 domain [63].…”
Section: Regulation Of Co-smad Stabilitymentioning
confidence: 98%
“…We compared the ability of a wild-type Med transgene (Med-wt) to rescue faf and Med dominant maternal enhancement of dpp hr4 with the rescuing ability of a ubiquitinresistant Med transgene. Our phylogenetic analysis showed that Lys 519 in human Smad4 (targeted by Ecto and USP9X) is conserved as Lys 738 in Med (Konikoff et al, 2008). For the non-ubiquitylatable Med transgene, we assumed the homologous lysine was the Faf target and created Med-K738R.…”
Section: Medea Lys 738 Is Deubiquitylated By Maternal Faf During Dpp mentioning
confidence: 99%
“…This hypothesis is supported by studies in Drosophila where expression of Xenopus Ecto led to phenotypes similar to mutations in Med that were rescued by co-expression of Drosophila Faf (Dupont et al, 2009). In addition, sequence analysis (Konikoff et al, 2008) found that a conserved lysine (Lys 519 in human Smad4; Lys 738 in Med) is the residue through which Ecto and USP9X regulate Smad4 activity (Dupont et al, 2009). To date, no developmental roles for Faf in TGF signaling have been identified via mutational analyses in any species.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, this topic has been addressed through the use of phylogenetics (Konikoff et al, 2008). Before reviewing this and other phylogenetic studies of TGFb pathway regulation, we reprise the traditional role of phylogenetics and provide the first description of the evolutionary relationship between TGFb family members based on full-length protein sequences.…”
Section: Reviewmentioning
confidence: 99%
“…In the case of TGFb type I receptor ubiquitylation, the specific lysines targeted by E3 ubiquitin ligases are unknown. To aid in the identification of lysines that become ubiquitylated in these receptors, Konikoff et al conducted a phylogenetic analysis of lysine conservation in type I receptors using the three-species strategy (Konikoff et al, 2008) (Fig. 4; see Table S2 in the (Pyrowolakis et al, 2008) and M. musculus (Mm, 33) (Derynck and Miyazono, 2008b) were aligned in Clustal X.…”
Section: Type I Receptor Sumoylationmentioning
confidence: 99%